The training and development process during childhood and adolescence of a multiple Ballon d'Or-nominated soccer player - Tønnessen, E.; Sandbakk, S. B.; Apold-Aasen, S.; Sandbakk, Ø.; Haugen, T. A. (Frontiers in Sports and Active Living, 2025)
Introduction: Information regarding the training and development of youth talents who successfully progress to professional soccer remains both limited and contradictory. The aim of this study was to retrospectively investigate the training and development process of a world-class soccer player during childhood and adolescence.